A Defense of the Phenomenological Account of Health and Illness. Issue 4 (29th July 2019) - Svenaeus, Fredrik
Abstract: A large slice of contemporary phenomenology of medicine has been devoted to developing an account of health and illness that proceeds from the first-person perspective when attempting to understand the ill person in contrast and connection to the third-person perspective on his/her diseased body. A proof that this phenomenological account of health and illness, represented by philosophers, such as Drew Leder, Kay Toombs, Havi Carel, Hans-Georg Gadamer, Kevin Aho, and Fredrik Svenaeus, is becoming increasingly influential in philosophy of medicine and medical ethics is the criticism of it that has been voiced in some recent studies. In this article, two such critical contributions, proceeding from radically different premises and backgrounds, are discussed: Jonathan Sholl's naturalistic critique and Talia Welsh's Nietzschean critique. The aim is to defend the phenomenological account and clear up misunderstandings about what it amounts to and what we should be able to expect from it.